Extensibility and Distensibility of the Thoracic Aorta in Patients with Aneurysm. (February 2017) - de Beaufort, H.W.L.; Nauta, F.J.H.; Conti, M.; Cellitti, E.; Trentin, C.; Faggiano, E.; van Bogerijen, G.H.W.; Figueroa, C.A.; Moll, F.L.; van Herwaarden, J.A.; Auricchio, F.; Trimarchi, S.
Abstract : Objectives: Reference values of aortic deformation during the cardiac cycle can be valuable for the pre-operative planning of thoracic endovascular aortic repair (TEVAR) and for facilitating computational fluid dynamics. This study aimed to quantify normal aortic extensibility (longitudinal extension) and distensibility (radial expansion), as well as pulsatile strain, in a group of 10 (>60 years) individuals with abdominal or thoracic aortic aneurysms. Methods: ECG gated CT images of the thoracic aorta were reconstructed into virtual 3D models of aortic geometry. The centre lumen line length of the thoracic aorta and three longitudinal segments, and the aortic diameter and luminal areas of four radial intersections were extracted with a dedicated software script to calculate extensibility, longitudinal strain, distensibility, and circumferential area strain. Results: Mean extensibility and longitudinal strain of the entire thoracic aorta were 3.5 [1.3–6.8] × 10 −3  N −1, and 2.7 [1.0–4.5]%, respectively. Extensibility and longitudinal strain were most pronounced in the ascending aorta (20.6 [5.7–36.2] × 10 −3  N −1 and 15.9 [6.6–31.9]%) and smallest in the descending aorta (4.4 [1.6–12.3] × 10 −3  N −1 and 2.2 [0.7–4.7]%). Mean distensibility and circumferential area strain were most pronounced at the sinotubular junction (1.7 [0.5–2.9] × 10 −3  mmHg −1 and 11.3 [3.3–18.5]%, respectively). Distensibility varied between 0.9 [0.3–2.5] × 10 −3  mmHg −1 and 1.2 [0.3–3.3] × 10 −3  mmHg −1 at the intersections in the aortic arch and descending aorta. Conclusions: Pulsatile deformations in both longitudinal and circumferential directions are considerable throughout the thoracic aorta. These findings may have implications for pre-operative TEVAR planning and highlight the need for devices that can mimic the significant aortic longitudinal and circumferential strains.